Journalism Training: Developing Teacher Professional Competence at SMK Negeri 1 Warungasem - Farida, Farida (JPGI (Jurnal Penelitian Guru Indonesia), 2023)
Journalism is an activity consisting of gathering news material (covering), reporting events (compiling), writing news (writing), editing news scripts (editing), and presenting or disseminating news (publishing/broadcasting) through the media. The purpose of journalistic training in general is an effort to improve current or future performance by imparting knowledge, changing attitudes, or improving the skills and quality of human resources. The material that will be presented in this training is how to write good articles, namely: 1) determining ideas, 2) determining themes, 3) compiling an article framework, 4) looking for credible references or references, 5) adding illustrations or pictures, 6) adding tables or graphs, 7) re-reading articles, 8) making interesting titles. When teacher articles are published in the mass media, in addition to receiving a fee, you can also apply for a credit score for the promotion of the teacher concerned(Keywords : Journalism, writing good articles, credit score)